Pengembangan Prototype Kotak Obat Otomatis Berbasis IoT untuk Pemantauan dan Pengingat Konsumsi Obat - Radika, Putu Dendy Kayoana; Putra, Made Adi Paramartha; Permana, Putu Trisna Hady (Jurnal Komtika (Komputasi dan Informatika), 2026)
The smart medicine box is a modern solution designed to assist users in managing their medication schedules consistently and on time. This study aims to design an automated reminder and medicine dispensing system based on the Internet of Things (IoT) using an ESP32 microcontroller. The system is connected to a Firebase Realtime Database to store and display data in real-time through a web interface built with Next.js. The device is equipped with a stepper motor, I2C LCD, buzzer, and a manual button that functions as a mechanism for refilling medicine. Testing was conducted using the black-box method to ensure all features functioned properly. The implementation results show that the system successfully performs medicine time reminders, automatic dispensing, and history logging. It is expected that this system can be further developed to enhance user convenience, improve adherence to medication schedules, and ensure reliable remote monitoring through the website platform.